2001
DOI: 10.1088/0963-0252/10/3/312
|View full text |Cite
|
Sign up to set email alerts
|

Cinematic of the current sheet in a pulsed coaxial plasma source operated with uniform gas filling

Abstract: The evolution of the plasma obtained from magnetic probes and other electrical measurements in a coaxial gun with a Ti central electrode (cathode) used for coating studies in a mbar N 2 atmosphere is given. The results indicate that the currently used snowplough models adequately describe the cinematic of the plasma current sheet only if an additional mass to that of the gas between electrodes is included in the plasma sheet. The need to include extra mass is taken as evidence of relevant erosion of the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It is then reasonable to explore whether this model can be extended to reproduce qualitative features of the sheath structure in the same operational regimes; this forms the focus of the next section. Conversely, when the GV model predictions do not match experimental data, it probably means that phenomena other than the snowplow effect are playing an important role; the discrepancy may then serve as a diagnostic tool [22].…”
Section: Algorithmic Aspects and The Physical Meaning Of The Gv mentioning
confidence: 99%
See 2 more Smart Citations
“…It is then reasonable to explore whether this model can be extended to reproduce qualitative features of the sheath structure in the same operational regimes; this forms the focus of the next section. Conversely, when the GV model predictions do not match experimental data, it probably means that phenomena other than the snowplow effect are playing an important role; the discrepancy may then serve as a diagnostic tool [22].…”
Section: Algorithmic Aspects and The Physical Meaning Of The Gv mentioning
confidence: 99%
“…The Buenos Aires Group has compared this model with experiments [21] and has shown a reasonably good agreement, which can be further improved in principle by incorporating adjustable parameters in the spirit of the Lee model [2]. This approach has been used to estimate electrode erosion in a coaxial gun [22] used for material coating applications. In spite of some of its positive features, the GV model has not been extensively used by DPF community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We may make an estimate of effective case II model parameters based on PF system parameters via the planar ''snow plow'' model 15,16 of plasma accretion used in conjunction with a more detailed planar model 17 that provides self-similar solutions to the accretion layer's density profile. The former assumes that the layer is thin enough to neglect its internal structure for the purposes of overall momentum and mass conservation.…”
Section: Plasma Focus Applicationmentioning
confidence: 99%
“…During the displacement, the shape of the current sheath (CS) changes, inducing variations on the boundary conditions, the forces and the dissipation rates. Under certain circumstances, local instabilities that perturb the movement of the CS have been observed, leading to toroidal structures [1][2][3]. Lee et al [1] observed a toroidal structure in the CS, by means of electrical probes, in a 1.5 kJ Plasma Focus.…”
Section: Introductionmentioning
confidence: 99%